Effect of fruit age and post-harvest period of cucumber on stored seeds - Barbedo, Claudio José; Barbedo, Adeliana Saes Coelho; Nakagawa, João; Sato, Osvaldo (Pesquisa Agropecuaria Brasileira, 1999)
Seeds from two cucumber (Cucumis sativus L.) cultivars, Pérola and Rubi, were evaluated in relation to physiological quality to verify the effects of age and postharvest period of fruits on seed storage potential. Fruits were harvested from 15 ('Rubi') or 20 ('Pérola') to 45 days after flowering and mantained in postharvest for 0, 5, 10, and 15 days before seeds extraction, at room conditions. Seeds were dried and stored in paper bags at room conditions for two and three years. Before and after the storage periods, samples were taken to germination and vigour tests. Results showed that immature seeds (extracted from immature fruits - 30 days after flowering) without post-harvest period, did not germinate at second year. However, seeds with high germination at initial test, from either ripe fruits (40-45 days) or immature fruits (30-35 days) with 10 or 15 days of post-harvest, mantained high germination (more than 70%) after three years of storage.